Airway Fire - Mojca Remskar Konia; Xan Jacobs; Richard Prielipp; Troy Reihsen; Robert Sweet; Ken Wangen (Association of American Medical Colleges, 2012)
Abstract Introduction An anesthesiologist must have a thorough understanding of situations that expose the patient to the risk of operating room fire (including airway fire). Our scenario presents a patient with acute respiratory distress syndrome who desaturates quickly with lower inspired oxygen concentrations. The anesthesia provider is forced to weigh the risks and benefits of higher oxygen concentrations, communicate with the surgical team, and recognize and manage the airway fire in real time as it occurs. Central to this experience is understanding conditions that increase the risk of airway fire, steps that need to be taken if airway fire occurs, and management of the patient after the airway fire has been extinguished. Methods The course is designed to allow learners/participants to manage an airway fire in the operating room. The scenario is based on the rare but serious event of airway fire induced with electrocautery during tracheostomy. The scenario allows learners to practice skills of prevention and management of airway fire. A PowerPoint presentation and video demonstration of how to simulate smoke in the airway are included. Also included is a PowerPoint presentation used during a didactic session. Results We have used the simulation scenario with 20 learners (anesthesiology residents CA-1, CA-2, CA-3), who received it with enthusiasm. They rated the experience highly and appreciated the hands-on experience with a critical event like airway fire. Learner feedback did not provide any useful suggestions for changes to the scenario. Discussion Airway fire is an emergent situation that occurs infrequently in the operating room but can have significant morbidity and mortality. It is therefore important for every anesthesia provider and every operating room team member to be able to manage this complication.